EFFICIENCY ANALYSIS OF PRODUCTION FACTORS UTILIZATION IN RICE FARMING IN SAWAH LUHUR URBAN VILLAGE KASEMEN SUBDISTRICT - Johan Setiawan; Achmad Fauzan Azhar (CV. Adiba Aisha Amira, 2025)
Rice plants are an important commodity, particularly in Indonesia, but their productivity often fluctuates. These fluctuations can be attributed to the use of production factors by farmers. This study aims to determine the impact and efficiency of the use of production factors (seeds, labor, pesticides, and fertilizers) in rice farming in Sawah Luhur Urban Village. The type of research conducted is quantitative descriptive research through a survey. The location selection was done intentionally or purposively. The chosen research location is Sawah Luhur Urban Village, Kasemen Subdistrict, in the Municipality of Serang, Banten, which is the largest rice producer in Kasemen Subdistrict. The research instrument used was a questionnaire, and the data collection methods used were interviews and observations. The study involved 90 respondents selected through simple random sampling. Data were processed using the Cobb Douglas production function with multiple regression analysis and price efficiency analysis methods. The results of this study indicate that 1) the simultaneous use of seeds, labor, pesticides, and fertilizers significantly affects production output where it is indicated by the F test statistic which has a value greater than th F critical value. Partially, only the use of fertilizers has a significant impact this is indicated by only the fertilizer having a calculated t test statistic greater than the t critical value. 2) The efficiency of using seeds, labor, and pesticides as production factors is inefficient, while the use of fertilizers is not yet efficient.